Isometric blood flow restriction exercise: acute physiological and neuromuscular responses - Benedikt Lauber; Daniel König; Albert Gollhofer; Christoph Centner (BMC, 2021)
Abstract Background Numerous studies have demonstrated that the addition of blood flow restriction (BFR) to low-load (LL) resistance exercise leads to elevated levels of muscle hypertrophy and strength gains. In terms of main underlying mechanisms, metabolic accumulation and increased neuromuscular adaptations seem to play a primary role. However, this evidence is largely based on dynamic exercise conditions. Therefore, the main objective was to investigate the acute physiological adaptations following isometric LL-BFR exercise. Methods Fifteen males participated in this cross-over trial and completed the following sessions in a random and counterbalanced order: isometric LL-BFR exercise (20% maximum voluntary contraction, MVC) and load matched LL exercise without BFR. Lactate levels, muscle activation as well as muscle swelling were recorded during the whole exercise and until 15 min post completion. Additionally, changes in maximal voluntary torque and ratings of perceived exertion (RPE) were monitored. Results During exercise, EMG amplitudes (72.5 ± 12.7% vs. 46.3 ± 6.7% of maximal EMG activity), muscle swelling and RPE were significantly higher during LL-BFR compared to LL (p < 0.05). Lactate levels did not show significant group differences during exercise but revealed higher increases 15 min after completion in the LL-BFR condition (LL-BFR: + 69%, LL: + 22%) (p < 0.05). Additionally, MVC torque significantly decreased immediately post exercise only in LL-BFR (~ − 11%) (p < 0.05) but recovered after 15 min. Conclusions The present results demonstrate that isometric LL-BFR causes increased metabolic, neuromuscular as well as perceptual responses compared to LL alone. These adaptations are similar to dynamic exercise and therefore LL-BFR represents a valuable type of exercise where large joint movements are contraindicated (e.g. rehabilitation after orthopedic injuries).